Experimental and Numerical Studies on Tire Tread Block Friction Characteristics Based on a New Test Device - J. Wu; Y. S. Wang; B. L. Su; Q. Liu (Advances in Materials Science and Engineering)
A new device was developed for tire tread block slip friction tests. Then the friction characteristics were investigated under different loads and contact roads. Based on this, a friction model for contact between tire tread block and different road surfaces was developed. A finite element slip friction model of rubber block was developed for studying the tread contact stress, stiffness under different pattern slope angles, and ditch radius. Results indicate that friction coefficient between tread and ice road increases when the temperature decreases; different tread patterns have a certain influence on the friction coefficient; its average difference was less than 10%. Different roads impact the coefficient of friction more significantly; the greater the pattern slope, the greater the radial stiffness.